Ancient Egypt : the land of pyramids and pharaohs - Horning, Nicole (World history series., 2018)
Offers a series of essays offering information on ancient Egypt, with opposing viewpoints on things like Egypt's origins, the meaning of the pyramids, and how the reign of the pharaohs came to an end.